PERBANDINGAN PERTUMBUHAN DAN KADAR PROTEIN IKAN NILA DIBERI PAKAN ALAMI DAN PAKAN BUATAN - Novita, Ria - (STKIP PGRI Sumbar, 2014)
The availability of food in sufficient quantities, on time, and good nutritional value is onevery important factor in fish farming activities. Food that can be given to Oreochromis niloticusfeed in the form of natural and artificial feed (pellets) which is used by fish farmers for fishfarming, therefore, carried out the research with the aim to determine Comparison of growth andprotein content of Oreochromis niloticus fed natural and artificial feed. This research wasconducted in the area of Asam Kamba District of Bayang District of Pesisir Selatan in March toMay 2014 and the analysis performed on Laboratory protein content of Chemistry, StateUniversity of Padang. This study is an experiment by using two treatments, A (natural feed) B(artificial feed) This study was conducted for 8 weeks to see the growth and protein content ofOreochromis niloticus. Data were analyzed statistically with the t test. The results showed thatthe artificial feeding can increase the growth of Oreochromis niloticus faster than the natural food.The highest protein content was found in Oreochromis niloticus fed naturally while the proteincontent was lowest for the Oreochromis niloticus fed artificial. So the natural food and artificialdiets can be used for fish farming.